Re-evaluating the Digital Gaming Profiles of Children and Adolescents during the COVID-19 Pandemic: A Comparative Analysis Comprising 2 Years of Pre-Pandemic Data - Çakıroğlu, Süleyman; Soylu, Nusret; Görmez, Vahdet (Addicta: The Turkish Journal on Addictions, 2021)
In this study, we aimed to examine the technology use behaviors and problematic gaming profiles of children and adolescents during the coronavirus disease 2019 pandemic lockdown period. We compared the findings with data collected before the pandemic. The Internet Gaming Disorder Questionnaire (IGDQ) was distributed online to students aged 10 to 18 years. More than half of the participants (54%) spent more time playing digital games during the pandemic. Compared with the data from May 2018, the time spent playing digital games and the total score of the IGDQ were significantly higher in boys than in girls (p